Lessons from experience: ESL student teachers' reflection during practicum through reflective journals - Intan Safinas Mohd Ariff Albakri; Mohd Hassan Abdullah; Ahmad Jazimin Jusoh (Studies in English Language and Education, 2017)
Reflection is a prospective alternative in exploring student teachers’ thinking during practicum. The data gained from student teachers’ reflection are significant in informing teacher education programs on how to equip pre-service teachers to become quality teachers. It is also crucial in addressing issues and conflicts highlighted by student teachers when they interact with the real context. This study is conducted with six semester seven student teachers undergoing their Bachelor in Education with honors Teaching English as a Second Language (TESL) program. The student teachers were asked to write reflective journal entries throughout the 14 weeks of their teaching practicum experience. The aim of the study is to identify the focus of the student teachers’ reflection and the challenges faced by them during practicum. Data were gathered using the reflective journal entries and semi-structured interviews with all the participants. The data were analyzed according to emerging themes. The findings indicated that the student teachers focus on three main themes in their reflections, which are managing learning, pedagogy and teacher attributes. While the challenges highlighted were difficulty in socializing with members of the institution, lack of professional support and lack of ability to manage a classroom.